حماية الحق في سرية المراسلات في ظل التطور التكنولوجي للمعلومات - د .سيفان باكراد ميسروب (PROSPECTIVE RESEARCHES, 2023)
The right of secrecy of correspondence is considered one of the personal rights which are connected with human personality and it has gained a prominent significance in the life of nations and people. Due to its importance, states and different legal systems have started to devote the practicing of this right through their international and regional conventions and their constitutional documents. Therefore, any violation of the secrecy of correspondence means a violation of the private life of individuals, particularly under the technological development of information and communication. Monitoring the mail, e-mail and phone calls constitute a risk on the privacy of man and his personal correspondence, a matter that requires much more care for being one of the vital and developed issues under the deficiency of traditional criminal laws as well as the absence of legislations in most of the Arab states regarding the violation of e-mail correspondence secrecy as being one of the most recent means of communication and correspondence; besides many of these countries have appealed to constrain practicing it on the pretext of preserving security and public order particularly in exceptional conditions.